Ibn 'Arabi's View on Love - M. Mansur (Postgraduate Program, Universitas Islam Negeri (UIN) K. H. Abdurrahman Wahid Pekalongan, Indonesia, 2017)
Scholars seem to have been interested in the world of Sufism since long time ago. Some of them have begun to study about Sufism deeply, and the results are different; some of them have gotten objective one but unfortunately, some have been mistaken. Ibn â€˜Arabi is one of the prominent Sufis whom they put as the object study. He is indeed controversial for his statements. However many Sufis entitled him as the great master, â€œSyaikh Al-Akbarâ€, the title which never been given to any Sufis after him and before him. Recently his thought has been regarded carrying on it the idea of pantheism, transcendentalism, and even pluralism. Some scholars use his oft-quoted ode which contains that he followed â€œreligion of loveâ€, â€œâ€¦Adinu Bidin Al Hub Anna Tawajjahat Rakayibuhu Fal Hubbu Dini Wa Imaniâ€¦â€, to back up their concept. According to them no matter what religion it is, as long as it stands on love, those religions lead to the same summit. And this would have to be revised for Ibn â€˜Arabi never meant that. Based on the case mentioned above, the writer tries to study Ibn â€˜Arabiâ€™s thought especially about his view on love to find out whether that accusation on him true or false. To get better result in his study, the writer collects some data which are related to this study which consist of Ibn â€˜Arabiâ€™s works and some other commentaries on him written by some scholars. Later, those data will be analyzed using integrated methods i.e.; descriptive method, analytical method, and critical method. The writer concludes some important points which have to be noticed well. That Ibn â€˜Arabiâ€™s entire concepts are based on his wahdatul wujud includes his concept of love. As well as his wahdatul wujud, his view on love doesnâ€™t stand for any idea of pantheist nor transcendentalist, nor even pluralist. According to him, Allah SWT is the source of all love which evokes another love that he divided into four divisions. And then he discussed that love is such fitrah of poverty (al iftiqar) toward Allah SWT which exists in the deepest of human soul, and it is beauty which make people love Allah SWT because He Almighty is beautiful. Further, Ibn â€˜Arabi stated emphatically that he followed â€œreligion of loveâ€ which refers to religion (al din) based on love brought by Muhammad SAW for Allah SWT loves Him SAW. Finally, the writer comes to a conclusion that to love Allah SWT is to love His Almighty Messenger, Muhammad SAW, because it is the essence of loving Him Almighty. And to love Muhammad SAW is to follow his orders and to stay away from his prohibitions which are written in his laws (syariâ€™at) which determined by Allah SWT. Thus, what Ibn â€˜Arabi and other Sufis as such Al Ghazali suggested in their works.